(NwOKALXNYE FORMY(B. s (NtEORIQs - (Nw(B. (NwASINA(B- (NgROSSMANs ((NmOSKWAs (NmUZYKALXNOEs, 1963)
(NwOKALXNAQ MUZYKA(B- (NMUZYKA DLQ GOLOSA (B- (NSAMYJ DREWNIJ WID MUZYKALXNOGO ISKUSSTWAW ROSESNICF ^ELOWE^ESKOJ RE^I(B.s
Keywords: (NtEORIQ(B.s